2021
DOI: 10.1111/pbi.13742
|View full text |Cite
|
Sign up to set email alerts
|

Genome and systems biology of Melilotus albus provides insights into coumarins biosynthesis

Abstract: Summary Melilotus species are used as green manure and rotation crops worldwide and contain abundant pharmacologically active coumarins. However, there is a paucity of information on its genome and coumarin production and function. Here, we reported a chromosome‐scale assembly of Melilotus albus genome with 1.04 Gb in eight chromosomes, containing 71.42% repetitive elements. Long terminal repeat retrotransposon bursts coincided with declining of population sizes during the Quaternary glaciation. Resequencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 114 publications
0
25
0
Order By: Relevance
“…The genome sequences [36] and RNA-seq data [61,62] of M. albus was obtained from College of Pastoral Agriculture Science and Technology, Lanzhou University. GRAS gene sequences of A. thaliana and M. truncatula are downloaded from the Phytozome database (https://phytozome.jgi.doe.gov/pz/portal.html, accessed on 5 February 2022) for searching and identifying GRAS sequences in M. albus genome.…”
Section: Identification Of the Gras Genes In M Albusmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome sequences [36] and RNA-seq data [61,62] of M. albus was obtained from College of Pastoral Agriculture Science and Technology, Lanzhou University. GRAS gene sequences of A. thaliana and M. truncatula are downloaded from the Phytozome database (https://phytozome.jgi.doe.gov/pz/portal.html, accessed on 5 February 2022) for searching and identifying GRAS sequences in M. albus genome.…”
Section: Identification Of the Gras Genes In M Albusmentioning
confidence: 99%
“…However, the whole genome analysis and function of GRAS family have not been reported in M. albus. In this study, using the latest available genome assembly and annotation database of M. albus [36], we comprehensively analyzed 55 GRAS genes by investigating physical and chemical properties, phylogenetic relations, gene duplication events, gene structures, motif compositions, chromosomal locations and cis-elements in promoter regions. Moreover, we explored the expression patterns of the MaGRAS genes in different tissues, ABA treatment, salt and drought stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that H 2 O 2 , proline, malondialdehyde (MDA) and soluble sugar can be used as indicators to evaluate drought resistance in plants [ 60 ]. Our previous study found that under drought stress, the content of H 2 O 2 peaked up to 24 h and the content of malondialdehyde (MDA), proline, and soluble sugar increased continuously up to 48 h, while the soluble protein content remained basically unchanged for 24 h and then decreased significantly [ 24 ]. So, in this study, we used 20% PEG6000 to simulate the drought stress and set different time points within 24 h [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mainly distributed in northwest, north, and northeast China, it has the characteristics of strong vitality, wide adaptability, fast reproduction, high seed yield, and strong nitrogen fixation ability [ 23 ]. In particular, the M. albus (2n = 16) genome and transcriptome were sequenced, and the first high-quality genome was recently published [ 24 ]. The publication of this genome provides information on M. albus genotypes and permits genome-wide research on this species.…”
Section: Introductionmentioning
confidence: 99%
“…The study on the functions and regulatory mechanism of the genes related to abiotic stress response in M. albus is of great significance to the stress-resistant molecular-assisted breeding of M. albus . At present, the genome sequencing of M. albus has been completed ( Wu et al, 2022 ), which lays the foundation for the systematic evolution and functional analysis of the BBX gene family of M. albus utilizing bioinformatics. In this study, for the first time, we systematically identified the MaBBXs at the genome level in the M. albus and performed their exon-intron structure analysis.…”
Section: Introductionmentioning
confidence: 99%